Just got this data sufficiency on a GMAC practice test and : DS Archive
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 19 Jan 2017, 02:04

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Just got this data sufficiency on a GMAC practice test and

Author Message
Intern
Joined: 11 Nov 2007
Posts: 4
Followers: 0

Kudos [?]: 0 [0], given: 0

Just got this data sufficiency on a GMAC practice test and [#permalink]

### Show Tags

11 Nov 2007, 13:33
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Just got this data sufficiency on a GMAC practice test and was wondering if anyone could help me with the explanation.

In the rectangular system are the points (r, s) and (u. v) equidistant from the origin?

1- r + s = 1

2- u= 1-r and v= 1-s

Any help would be greatly appreciated. Thanks
Director
Joined: 11 Jun 2007
Posts: 647
Followers: 6

Kudos [?]: 288 [0], given: 0

### Show Tags

11 Nov 2007, 14:32
I think (C)

basically, we have to find if r^2 + s^2 = u^2 + v^2 (distance from (r,s) to origin = distance from (u,v) from origin).

r^2 + s^2 = u^2 + v^2 can be written as:

(r + s)^2 - 2rs = (u + v)^2 - 2uv

we know r + s = 1; u + v = 1;

Therefore, 1 - 2rs = 1 - 2uv.

If we can prove that rs = uv using the three equations:

r + s = 1;
r + u =1;
s + v = 1;

then (C) is the right answer. Let's see if that is the case.

rs = uv --> rs = (1-r)(1-s)
i.e. rs = 1 - r - s + rs;
--> r + s = 1; which is true. Therefore uv = rs.

Hence (C).
11 Nov 2007, 14:32
Display posts from previous: Sort by